Legg-Calve-Perthes disease: Methods of treatment - Benavente Arce, Fernando (1992)
It is reviewed the actual concepts about concepts about legg-Calvé-Perthes disease, and observe that too long period of inmovilization of the affected hip produces psychologic problems in the patients and their family, and the functional results are not supperior compared with other methods.  In this work we compare the personal results of three methods of containment of the femoral head within the acetabulum using abduction casts in patients with Catterall III-IV Perthes disease: Inhauser in 27 patients (32 hips), Petrie in 10 patients (11 hips), Broom Stick in 8 patients (9 hips); despite the short period of follow up we obtained better results with Petrie and Broom Stick casts, Improving first the motion with skin traction and physical therapy. The results were rated using the system of Stulberg.